Education through play in the field of music: Contribution of Montessori method - Ivanović Marija K.; Sudzilovski Danijela M (University of Kragujevac - Faculty of Pedagogy, Užice, 2018)
An important area of modern education is music education, through which children acquire knowledge and skills. Music is also an important tool that fosters the development of personality, intellectual, physical and psycho-motor development, the development of language, emotional and social development. It also represents the means by which the individual expresses himself. Since the idea of modern education is to keep the child at the forefront of attention, it is supposed to use methods that facilitate learning, develop creativity and encourage research among children. Those methods should also encourage children to participate actively in the process of learning and acquiring knowledge. A play appears as spontaneous activity that is fun and initiated by desire of child, with flexible rules. A child is playing even if it is not aware of the motive of its activity. In educational terms the greatest value of play is that it is able to attract and keep the children's attention on intended contents, as well as to motivate them to participate actively in certain activities. Therefore, some educators today call for a constructivist approach to education-education through play. Because of playful activities and sensory didactic materials, the idea of freedom and of child who "builds" itself, the method of Maria Montessori can be used to improve the education in the field of music. The paper discusses education through play at preschool age in the field of music on the example of Montessori method.